Explorations 1 Grammar for the Experienced Beginner - Caisee, Susan; Rueda, Jennifer; Emens-Hesslink, Kristee (Open textbook library., 2021)
Welcome to Explorations 1: Grammar for the Experienced Beginner. This English grammar textbook was designed for a class of Clackamas Community College (CCC) ESOL students who need only a review of the BE verb and are ready to learn the simple present and present progressive tenses. This textbook has four chapters. Each chapter covers a grammatical point/component/element. Chapter 1 is a review of the BE verb. The BE is special and has its own rules (different from other verbs). Chapter 2 is the Present Progressive tense. This is the tense we use when we are talking about things happening now or near now. Chapter 3 is the Simple Present Tense. We use the Simple Present Tense to talk about facts, routines, and habitual activities. Chapter 4 is a comparison of chapter 3 and 4.